Five‐year results of a modified left atrial maze IV procedure in the treatment of atrial fibrillation: a randomized study. Issue 4 (19th November 2019) - Zhang, Dengshen; Shi, Jun; Quan, Huayan; Liu, Lu; Zhang, Jian; Guo, Yingqiang
Abstract: Background: The left atrial maze IV (LAM‐IV) alone has been used to eliminate atrial fibrillation (AF) without severe right heart diseases. However, we felt that it could be improved and developed a modified LAM‐IV (MLAM‐IV). In this prospective trial, we aimed to investigate 5‐year clinical outcomes of AF in patients treated by the novel MLAM‐IV technique. Methods: Between September 2012 and October 2013, 120 patients who underwent valve surgery and bipolar radiofrequency ablation for AF were randomized into the LAM‐IV group ( n = 60) or MLAM‐IV group ( n = 60). At postoperative follow‐up examinations, data were recorded at 1, 3 and 6 months, and annually thereafter. Results: The mean ablation time and postoperative ventilation time were shorter in the MLAM‐IV group than in the LAM‐IV group ( P < 0.001 and P = 0.03, respectively). At 5 years, the rate of freedom from AF was 69.0% in the MLAM‐IV group and 60.0% in the LAM‐IV group (hazard ratio 0.71, 95% confidence interval 0.39 to 1.32, P = 0.42). There were no differences with respect to the early operative mortality and major complications, late mortality, and major adverse events. Conclusions: The MLAM‐IV provides a technically simpler ablation process. The MLAM‐IV was associated with less ventilation support in the early postoperative period. The long‐term efficacy of the MLAM‐IV in the treatment of AF is comparable to that of the LAM‐IV. Abstract : In this study, we aimed to investigate the outcomes of a modified left atrial maze IV procedure (MLAM‐IV) for the surgical treatment of AF. Results showed that the MLAM‐IV is technically simpler than the traditional left atrial maze‐IV (LAM‐IV) in the ablation process. The MLAM‐IV was associated with less ventilation support in early postoperative period. The long‐term efficacy of the MLAM‐IV in the treatment of AF is similar to that of the LAM‐IV.